Formation and Local Structure Analysis of High‐Valence Chromium Ion in Dicalcium Silicate. Issue 9 (3rd June 2016) - Suzuki, Masanori; Umesaki, Norimasa; Okajima, Toshihiro; Tanaka, Toshihiro
Abstract : Dicalcium silicate (2CaO·SiO2 ) is a typical silicate compound that exists even at elevated temperatures. Different types of elements can be dispersed in dicalcium silicate to form a solid solution phase. However, the dispersion behavior of transition elements that can display different ionic valences is not well understood. Herein, we investigate the local structure of chromium ions dispersed in dicalcium silicate of different phase states under inert and air atmospheres using Cr K‐edge X‐ray absorption near‐edge structure (XANES) spectroscopy and first‐principle calculations. The measured XANES spectra indicated that Cr ions exist as high‐valence states when dispersed in dicalcium silicate in air atmosphere. Specifically, Cr 6+ ions were detected in γ‐dicalcium silicate, which was prepared by annealing a mixture of 2CaO·SiO2 and Cr2 O3 at 973 K in air atmosphere. In addition, the XANES spectra obtained via first‐principle calculations revealed that Cr ions, with high‐valence states between Cr 4+ and Cr 6+, in dicalcium silicate, occupy the tetrahedral Si 4+ sites.